DAP and labour issues : what the English press did not publish (1976)
Commentary on speech by the opposition leader and DAP member of Parliament for Kota Melaka, Lim Kit Siang, in the Dewan Rakyat on 14th July 1976 on the Employment (Amendment) Bill 1976.